Avaliação externa de escolas em Minas Gerais: da escuta à possibilidade de desenho de um processo
External evaluation of schools is a common procedure in several countries and is even recommended by different international and supranational bodies. Its implementation and development result from the understanding of processes as drivers of improving educational quality and school autonomy, as well as an instrument for regulation and accountability, perspectives associated with the expansion of control mechanisms. In the European context, we observe the organization of different models, which are structured from each country's own perspectives, although presenting points of confluence between the actors responsible for their organization and implementation, the stages of the process, the degree of participation of the school community, the deadline for carrying out assessments, among others. In Brazil, the context in which this research is carried out, there is still no culture of institutional evaluation of schools, although mention of these processes is found in some regulations. In this context, the research developed and presented here aims to analyze the perspective of some actors in the Minas Gerais Education System on the possibility of developing a policy in this area in the state. Despite the vast literature and Brazilian experiences on educational assessment, the focus on learning assessments is predominant, and the discussion on the external assessment of schools in the country is still very incipient from an empirical, academic and even normative point of view. The research, using mixed methods, is built on a process of listening to school directors and inspectors, as well as central level managers. The data were interpreted considering the literature on educational evaluation and external evaluation of schools and the study of models adopted in Europe. The perceptions of these actors point to an optimistic view regarding the potential of school evaluation in terms of improving educational quality and the ability to provide information for the allocation of public resources. There is a favorable scenario for the possible construction of a model, which must be further explored, dialoguing with the actors involved, without considering the complexity of implementing a theme that is still in its infancy in the country, in a context of large dimensions, diversity and inequality.